A influência da cultura brasileira no desenvolvimento de fragrâncias - Oliveira, Jéssica Martinez (2018)
The main goal of this thesis is to assess how Brazilian culture influences the development of fragrances in cosmetic products. In addition, this research seeks to understand deeply how the process of developing the fragrance of a cosmetic product in Brazil works and to understand the factors that influence this process from a business perspective. As a theoretical foundation, several references were used in their fields and they deal in depth with the themes of culture, product development and smelled cosmetic products. Aiming to reach the expectations of this work, an in-depth research was carried out with eight cosmetics professionals working in large companies with high influence in the process of development. The results verified that the process is carried out in a structured way, however the understanding of aspects of consumer behavior must be considered more assertively to guarantee satisfaction and success of the new product.